LRFMV: an efficient customer segmentation model for superstores - Toyeb, Md.; Mahfuza, Rezwana; Islam, Nafisa; Emon, Md Asaduzzaman Faisal (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.